Exploring the Psychological and Relational Consequences of Smartphone Overuse in Marital Relationships - Lee, Sophia; Chen, Mei-Ling (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to explore the psychological and relational consequences of smartphone overuse in marital relationships. Methods and Materials: A qualitative research design was employed to gain in-depth insights into couples’ experiences. The study included 24 married participants residing in Taiwan, selected through purposive sampling to capture diverse marital backgrounds. Data were collected through semi-structured interviews, which allowed participants to articulate their perceptions and experiences regarding smartphone use within marriage. Interviews continued until theoretical saturation was reached, and each session lasted between 45 and 70 minutes. With participants’ consent, all interviews were audio-recorded, transcribed verbatim, and analyzed using NVivo 14 software. A thematic analysis approach was applied, with open coding followed by categorization and theme development, ensuring systematic identification of patterns and meanings in the data. Findings: The analysis generated four overarching themes: (1) Emotional Consequences, including stress, jealousy, mood dysregulation, and loneliness; (2) Relational Conflicts and Tensions, involving communication breakdown, trust issues, intimacy decline, and parenting disagreements; (3) Cognitive and Behavioral Patterns, encompassing habitual checking, compulsive use, time mismanagement, and escapism; and (4) Coping Strategies and Adaptive Responses, which included negotiating boundaries, rebuilding communication, joint digital activities, professional help-seeking, and emotional reconnection. Participants emphasized how smartphone overuse fostered feelings of neglect, suspicion, and conflict while also demonstrating the potential for constructive adaptations when couples actively addressed the challenges. Conclusion: Smartphone overuse significantly affects marital relationships by eroding intimacy, intensifying jealousy, and provoking conflict. At the same time, couples who implemented intentional strategies, such as setting boundaries and engaging in shared activities, demonstrated resilience and relational recovery. These findings underscore the dual role of smartphones as both relational stressors and potential tools for connection, highlighting the need for awareness, communication, and structured interventions in marital contexts.